Variabilidade da opacidade submilimétrica em escalas de minutos - Huamán, Kely Dorely Padilla (2021)
Water vapor is the main cause of atmospheric attenuation at high frequencies. The measurement the atmospheric optical depth ( ) allows us to obtain the true brightness temperature of an astrophysical object. Melo et al. (2005), used the solar brightness temperature as a reference to obtain the Atmospheric optical depth at sub-millimeter waves. Cornejo Espinoza (2017) used the same method for a longer period from 2006 to 2014. All these measurements were made with the Solar Telescope for Sub-millimeter Waves (SST), at the El Leoncito Astronomical Complex (CASLEO) at the submillimeter frequencies of 212 and 405 GHz. In this work we will use a new method to calculate the variation the Atmospheric optical depth in time scales from minutes to hours. We will use the opacities determined by the brightness and tipping methods as an input parameter, on days when the Sun does not have any active region. The method assumes that any observed intensity variation is then due to fluctuations in the observing direction.